Transnasal endoscopic medial maxillectomy: changing trend in the management of sinonasal inverted papilloma, report of two cases - Asha'ari, Zamzil Amin; Ahmed Khan, Shamim (Faculty of Medicine, International Islamic University Malaysia, 2007)
The current advents of endoscopic techniques have enabled rhinologists to treat inverted papilloma of the nose with a more favourable surgical morbidity. However the supposed changing trend in surgical management of sinonasal inverted papilloma from external approach to endoscopic technique has to come with caution as certain guidelines must be made to ensure its effectiveness. Since the introduction of purely transnasal endoscopic medial maxillectomy in 1981, many authors have published their experiences in this field. This article reviews some of the literatures regarding the management aspect of inverted papilloma particularly focusing on the endoscopic medial maxillectomy and relate with our own experience in management of this tumour endoscopically.